Labor and delivery care a practical guide - Cohen, Wayne R. (Wiley-Blackwell, 2011)
"Labor and Delivery: The hands-on guide provides practical and timely information to help guide the clinical care of women during pregnancy. An expert team of authors present the framework to integrate information obtained from hands-on evaluation of laboring women into logical matrix for decision-making and risk avoidance. By not focusing solely on explanations of the readings and usage of technology such as ultrasound and fetal monitoring, this experience-based guide to labor care concentrates on traditional skills of observation and careful physical examinations to help obstetricians care for women during labor while improving her experience of birth"--Provided by publisher.